Exploring novel insecticide candidates: Targeting Na[+],K[+] -ATPase in Drosophila melanogaster through computational and experimental approaches. - Wang, T.; Miao, J.; Chang, Y.; Liang, X.; Li, F.; Lu, H. (Journal of molecular graphics & modelling, 2025)
Pest infestations have been posing a serious and persistent threat to agricultural production. Traditional insecticides are currently confronted with a multitude of problems. The discovery of novel insecticide targets and the screening of active molecules can offer an entirely new direction for surmounting the limitations of traditional insecticides and lay a solid foundation for the development of highly effective insecticides with distinctive mechanisms of action. In this study, the Na[+],K[+]-ATPase of Drosophila melanogaster has been selected as the target. Its three-dimensional structure has been constructed via homology modeling, and the evaluation has indicated that its quality is reliable. Subsequently, techniques including virtual screening, molecular docking, and molecular dynamics simulation have been employed to screen compounds and investigate their mechanisms of action. The analysis of binding modes has demonstrated that hydrogen bonding and hydrophobic interactions have played a crucial role in the binding of ligands. Molecular dynamics simulations and calculations of binding free energies have shown that Compound 1 and Compound 2 have exhibited similar or even stronger affinities in comparison to known inhibitors. Residue decomposition free energy reveals the types of key amino acid residues involved in the interaction between these compounds and NKA. Preliminary bioactivity assays have verified the bioactivities of these compounds. Ouabain, Compound 1, Compound 2, and Compound 4 have shown significant delayed toxic effects, with Compound 4 having a more pronounced delayed effect. Our study has provided certain valuable ideas and insights for the development of new insecticide molecules targeting the Na[+],K[+]-ATPase of Drosophila melanogaster.